2016
DOI: 10.3892/ol.2016.4713
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5/STAT3 interaction mediates synergism of high salt with IL-17 towards induction of VEGF-A expression in breast cancer cells

Abstract: Chronic inflammation has been considered an important player in cancer proliferation and progression. High salt (sodium chloride) levels have been considered a potent inducer of chronic inflammation. In the present study, the synergistic role of high salt with interleukin (IL)-17 towards induction of the inflammatory and angiogenic stress factor vascular endothelial growth factor (VEGF)-A was investigated. Stimulation of MCF-7 breast cancer cells with high salt (0.2 M NaCl) and sub-minimal IL-17 (1 ng/ml) enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Briefly, total RNA was extracted from 10 6 cells using TRIzol reagent (Sigma–Aldrich, St Louis, MO) and analyzed as mentioned previously [7, 20, 21]. RNA samples were quantified by absorbance at 260nm.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, total RNA was extracted from 10 6 cells using TRIzol reagent (Sigma–Aldrich, St Louis, MO) and analyzed as mentioned previously [7, 20, 21]. RNA samples were quantified by absorbance at 260nm.…”
Section: Methodsmentioning
confidence: 99%
“…CDK5, c-Abl, and ATM promote the nuclear localization of NFAT5, and, in contrast, CK1 inhibits its nuclear accumulation [19]. There are many other factors that influence the activation and expression of NFAT5, such as inflammatory cytokines [16, 77], microRNAs [50, 62, 78, 79], and transcription factors [80-83]. …”
Section: The Regulation Of Nfat5 Activationmentioning
confidence: 99%
“…Numerous studies have revealed that the treatment of hypertension, targeted to RAS components (AT1 blockers, ACE inhibitors), is associated with the suppression of VEGF-A-mediated tumor development, better survival and a lower risk of the development of cancer (Yoshiji et al 2002;Dai et al 2015;Fan et al 2016). Moreover, a recent study implied that breast cancer cells increased the expression of VEGF-A after exposure to high NaCl levels compared to control cells (Amara et al 2016). In our experiment, we observed a significant positive correlation between the AT1 receptor and VEGF-A mRNA expression in the liver of the female control group.…”
Section: Discussionmentioning
confidence: 99%